The use of peppermint oil in the treatment of irritable bowel syndrome - Karol Mazur; Dominik Machaj; Dominika Mazur; Marlena Baran; Alicja Płaczek (Kazimierz Wielki University, 2020)
Irritable bowel syndrome (IBS) is a a chronic functional gastrointestinal disorder, that affects large intestine. The symptoms of IBS include: abdominal pain, discomfort, change in bowel habits and disordered defecation. The causes of irritable bowel syndrome  have not yet been fully investigated and determined. Peppermint (Mentha ×piperita) is a hybrid type of mint, a cross between watermint (Mentha aquatica) and spearmint (Mentha spicata). Peppermint oil is produced in the proces of steam distillation of fresh leaves of peppermint. The aim of this study was to evaluate the use of peppermint oil in the treatment of irritable bowel syndrome. Our study material consisted of publications, which were found in PubMed, ResearchGate and Google Scholar databases. The first step was to find proper publications from the last 30 years. The second step was to carry out an overview of the found publications. Based on the results of mentioned studies it can be concluded that peppermin oil is effective in the treatment of irritable bowel syndrome due to providing global symptom improvement  and significant reduction of abdominal pain, and its short-term use is safe. However, further research is needed to estabilish the role of peppermint oil in the treatment of irritable bowel syndrome and to determine the optimal duration of treatment, dosage of peppermint oil, and its possible side effects related to long-term usage.